Lyme Diseases. General Problems (I Part) - V.V. Mavrutenkov (Zaslavsky O.Yu., 2014)
Lyme disease (syn. Lyme-borreliosis, tick-borne or borreliosis) is the most common in Europe transmissive (tick-born) bacterial anthropozoonosis. Alfred Buchwald was the first to describe the late stage of the borreliosis 130 years ago. Contamination with B.burgdorferi s.l. occurs due to adhesion of the ticks I.ricinus and I.рersulcatus; with that human presents no epidemiological danger. Infectious process is determined by features of B.burgdorferi s.l. and genetically determined human immune response.